Development and characterization of high-throughput serological assays to measure magnitude and functional immune response against S. Paratyphi A in human samples - Carducci, Martina; Massai, Luisa; Lari, Elisa; Semplici, Bianca; Grappi, Silvia; Maria, Noshi; Jones, Elizabeth; Conti, Valentino; Piu, Pietro; Scorza, Francesco Berlanda; Iturriza-Gómara, Miren; Montomoli, Emanuele; et al. (Frontiers in Immunology, 2024)
Typhoid and Paratyphoid fever cause a global health burden, especially for the children of Southern Asia. The impact of the disease is further exacerbated by the dramatic increase of antimicrobial resistance. While vaccines against Salmonella Typhi have been developed and successfully introduced, an effective vaccine targeting S. Paratyphi A is still lacking. Several efforts are currently ongoing to develop vaccines targeting both S. Typhi and S. Paratyphi A. In order to analyze the immune response induced by vaccination and in sero-epidemiological studies, easy to perform and high throughput immunoassays are needed. Here we present the setup and characterization of a customized ELISA assay and of a luminescent-based serum bactericidal assay (L-SBA) to measure the quantity of S. Paratyphi O antigen specific antibodies and their functional activity against S. Paratyphi A. Robust quality control criteria have been put in place both for ELISA and SBA and assays have been fully characterized in terms of quantitation limit, limit of blanks, specificity, linearity and precision. Assays are being employed to analyze samples from clinical trials, enabling the assessment of immunogenicity during clinical vaccine development.